Determinan Pneumonia pada Balita di Kota Surabaya - Nilandita, Widya; Mustika, Ika (State Islamic University of Sunan Ampel, 2025)
Pneumonia was an infectious disease of the respiratory tissues and could be a leading cause of death in young children. Several risk factors contributed to an increased incidence of pneumonia, including the nutritional status of children, exclusive breastfeeding, immunization status, and environmental conditions both inside and outside the home. This study aimed to determine the relationship between environmental, nutritional, and socioeconomic factors with pneumonia in children under five in Surabaya. The research employed a case-control design with a population consisting of children diagnosed with pneumonia and those without pneumonia in the working area of the Surabaya Health Office, specifically at Wiyung Health Center and Gayungan Health Center. A total of 102 respondents were selected using purposive random sampling techniques. Data analysis was conducted using univariate, bivariate, and multivariate methods. The multivariate analysis utilized multiple logistic regression tests for determinant modeling. The results indicated that variables such as age, low birth weight (LBW), air temperature, air humidity, and light intensity had an impact on the incidence of pneumonia. Among these, air humidity had the greatest impact, with an odds ratio (OR) of 9.60. Children living in areas with inadequate air humidity were 9.60 times more likely to develop pneumonia compared to those living in areas with adequate humidity.